2017
DOI: 10.1515/mosr-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Social Responsibility: Example of Cycling Service

Abstract: The article presents research on consumer social responsibility based on the example of cycling service. The author analyses the tourism sector determining a relation between socially responsible behaviour of an organization and consumer behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…According to the fi ndings of previous studies consumers with higher income and education levels are more willing to support environmentally and socially responsible business practices of hospitality and tourism companies, however in case of Kazakhstani consumers we have received the controversial results opposite to this fact. The second and third hypotheses of the study were not confi rmed and the results of the test revealed that there was no correlation between the motivation to support responsible business practices and income as well as education level of respondents (Table 3 Willingness to be involved in sustainable consumption and responsible practices depends on individual's awareness about corporate social responsibility initiatives of hospitality fi rms [20]. As it has been shown by study results Kazakhstani consumers are willing to pay higher prices for environmental and socially friendly products and services as a result of personal level of sustainability awareness and such kind of behavior does not depend on income or education level of individuals.…”
Section: Research Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…According to the fi ndings of previous studies consumers with higher income and education levels are more willing to support environmentally and socially responsible business practices of hospitality and tourism companies, however in case of Kazakhstani consumers we have received the controversial results opposite to this fact. The second and third hypotheses of the study were not confi rmed and the results of the test revealed that there was no correlation between the motivation to support responsible business practices and income as well as education level of respondents (Table 3 Willingness to be involved in sustainable consumption and responsible practices depends on individual's awareness about corporate social responsibility initiatives of hospitality fi rms [20]. As it has been shown by study results Kazakhstani consumers are willing to pay higher prices for environmental and socially friendly products and services as a result of personal level of sustainability awareness and such kind of behavior does not depend on income or education level of individuals.…”
Section: Research Resultsmentioning
confidence: 92%
“…However, Craafl and [19] revealed that Christian religiosity except the Orthodox Protestant raises positive attitude towards socially responsible off erings. Jeseviciute-Ufartiene [20] divides responsible consumers into two categories:…”
Section: Main Partmentioning
confidence: 99%